If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-(x+1)=-2
We simplify the equation to the form, which is simple to understand
2x-(x+1)=-2
Remove unnecessary parentheses
2x-1x-1=-2
We move all terms containing x to the left and all other terms to the right.
+2x-1x=-2+1
We simplify left and right side of the equation.
+1x=-1
We divide both sides of the equation by 1 to get x.
x=-1
| -3.7(x-5.3)-5.3(7x-2.4)=-53.35 | | 8(n+3)=9n+3-6 | | 39k^4-9k^3/4 | | 3/5(7x+11+6x) | | 8(3)+3(0)= | | (-2x+3)=25 | | -4(m+5)= | | 2+8j= | | 5x-4(0)=15 | | 9x-2=7x+34 | | 5(3+.08y)-4y=15 | | 6-9/6*3+5*3 | | -5=4x^2-x | | 3a-17=4 | | 6-9/6/3+5*3 | | 7p^2+7p-7=0 | | 175-6=6x+19 | | 3x+12x=105 | | 2(-2)+9(1)= | | 6-9*6/3+5*3 | | 8x+3(1)=-13 | | 6x-5y=-1 | | 3z+2=8 | | 6+17d=13d+18 | | 8(2.5+-4.5y)+3y=-13 | | (6-j)(6+J)= | | -132x-7x=8x+18 | | x+(x+13823)=119453 | | -3x+5y=12 | | 320+8x=7208-220x | | 3(6+5y)=2(-5+5Y) | | 105-5x=9x+2 |